Research of the results of Ukrainian championships in rowing on ergmeters as a stage of selection for the national team I - Bondarenko, I; Twelina, A.; Andryushchenko, M.; Konoplyanik, O.; Mayer, V. (Physical Education Sports and Human Health, 2020)
As a result of studies, it was found a positive relationship between the time taken for a distance of 2000 m on an ergometer and the results of competitions on water (2000 m) for highly skilled athletes in rowing (rxy = 0.51-0.78) (P. Mikulic, 2009). Objective: Research of the results of competitions in rowing on ergometers among highly qualified rowers with the further identification of factors influencing the time taken to cover a distance of 2000 m. Material & methods: The study analyzed the performance of Ukrainian Championship participants: 11 athletes - Honored Masters of Sports of Ukraine, 14 - Masters of Sports of Ukraine of International Class, 53 - Masters of Sports of Ukraine, 30 - Candidates for Masters of Sports of Ukraine, 2 athletes - with 1 category, 1 - without category. The following methods were used: analysis of scientific sources and protocols of technical results of the Ukrainian Championship in rowing on ergometers. The methods of mathematical statistics that were applied are: Kolmogorov-Smirnov test, determination of the mean and standard deviation, correlation analysis. SPSS package was used for calculations. Results. For athletes of the open category average rowing time on ergometers, determined at a distance of 2000 m, was: for men - 376.71 s, for women - 437.50 s. Among lightweight athletes it was observed the following results: 401.12 s for men, 465.03 s for women. It was determined that the age of athletes correlates with the time for covering a distance of 2000 m: men - (r = - 0.633; p < 0.01), light-weight men - (r = - 0.677; p < 0.05), women - (r = - 0.554; p?0.01), lightweight women (r = - 0.618; p <0.05). It was determined the correlation between the body weight of men in the open category and time to overcome the distance of 2000 m and 5000 m: (r = - 0.317; p <0.05) and (r = - 0.388; p <0.01). The close relationships between the time of overcoming the distance of 2000 m and the distance of 5000 m were found in all groups of athletes: the open category for men (r = 0.928, p < 0.01) and women (r = 0.963, p <0.01); lightweight men (r = 0.975, p <0.01) and lightweight women (r = 0.978, p < 0.01). Conclusions. Thus, the age of the athlete and sports experience affect the results of competitions on ergometers. It has not been identified any significant effect of body weight on the result of competitions on rowing ergometers, except for male athletes of the open category. The formula of the regression equation is determined, which will allow predicting the time of passing the distance of 2000 m based on the result of the distance of 5000 m.